One Size Fits All: Context Collapse, Self-Presentation Strategies and Language Styles on Facebook. Issue 3 (6th April 2018) - Gil-Lopez, Teresa; Shen, Cuihua; Benefield, Grace A; Palomares, Nicholas A; Kosinski, Michal; Stillwell, David
Abstract: This study empirically examines context collapse on Facebook by examining audience influences on content and language in self-disclosures. Context collapse is the process of disparate audiences being conjoined into one. Using a public longitudinal behavioral data set of 6, 378 Facebook users, the study found that the size and heterogeneity of people's networks were positively associated with the number of text status updates they posted, but negatively associated with language style variability of these updates during 12 months. Results suggest that people manage their online self-presentation in ways that are consistent with lowest common denominator, imagined audience, and accommodation propositions. Network size was positively associated with the proportion of positive emotional language and negatively with negative emotional language, whereas heterogeneity had the opposite effect.